"HOURGLASS COLOBOMA": A CASE REPORT AND REVIEW OF ETIOPATHOGENESIS. Issue Volume 15:Issues 4(2021) (July 2021) - Kumar, Madhu; Shanmugam, Mahesh; Sagar, Pradeep; Kumar, Dilip; Konana, Vinaya Kumar
Abstract : Purpose: To report a rare case of multiple fundal colobomata and to review the possible etiopathogenic factors involved in its genesis. Method: Case report. Result: A 21-year-old myopic lady was noted to have 2 fundal colobomata—one in the inferior and the other in superior hemisphere of globe in a mirror-image fashion resembling an "hourglass" in the right eye and a typical Type 3 coloboma in the left eye. The iris was normal in both the eye. Multiple fundal colobomata have not been described in the literature. The presence of "accessory embryonic fissure" in the developing eyeball is the only probable mechanism that can explain this presentation. This case is an evidence for the possibility of presence of accessory embryonic fissure in developing eyeball in human. The eponym "hourglass coloboma" or "mirror-image colobomata" best describes this condition. Conclusion: This report of multiple fundal colobomata is the first of its kind. This case is an evidence for possibility of presence of accessory embryonic fissure in developing eyeball in human. Abstract : Atypical choroidal coloboma is a rare congenital malformation of eyeball, and various theories have been proposed to explain the genesis of such a clinical picture. According to our knowledge, multiple colobomata of choroid are not described in literature, and this is probably the first of its kind. This case provides evidence for the presence of accessory embryonic fissure in human embryo and adds to our current knowledge on the development of eyeball in human